2023
DOI: 10.1128/spectrum.00036-23
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing-Dependent Invasion of Ralstonia solanacearum into Fusarium oxysporum Chlamydospores

Abstract: Ralstonia solanacearum species complex (RSSC) strains infect both plants and fungi. The phc quorum-sensing (QS) system of RSSC is important for parasitism on plants, because it allows them to invade and proliferate within the hosts by causing appropriate activation of the system at each infection step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The vector was introduced and expressed in P. protegens Cab57 . The recombinant was named Cab57- cayG .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector was introduced and expressed in P. protegens Cab57 . The recombinant was named Cab57- cayG .…”
Section: Resultsmentioning
confidence: 99%
“…CayG (1.2 kb, containing NdeI- and Sal I-digestion sites, no codon optimization) was synthesized by Eurofins Genomics and inserted into a modified pDSK519 to create pCcayG. This plasmid was electroporated into Cab57 or Δ proA cells, and the kanamycin-resistant (50 μg/mL) recombinant was selected.…”
Section: Methodsmentioning
confidence: 99%
“…EPS I, the major extracellular polysaccharide in the RSSC, is a virulence factor in both Rs and Rps ; it is critical for colonization of the stem and vertical spread in the stem [33,35,36]. It has been assumed EPS I has a major role in Ralstonia biofilm development as it does in several well-studied bacteria and because it is a component of the biofilm ECM, but studies of static biofilm formation yielded mixed results [53,54]. To investigate this further in both static and flowing environments, we used an EPS I-deficient epsB mutant.…”
Section: Resultsmentioning
confidence: 99%
“…While RSSC strains produce copious amounts of EPS in vitro and in the stem at high cell densities, EPS has not been directly visualized in biofilms in planta [33,69]. A recent study on endoparasitism of Fusarium oxysporum showed EPS I is a core component of Rs biofilms on fungal hyphae [54]. In Rps OE1-1, EPS I contributes to biofilm formation on PVC plates but contrarily, an EPS I-deficient mutant formed a similar number of mature biofilms in ex vivo apoplastic fluid [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…1 × 1 mm 2 agar) or F. oxysporum NBRC 31213 , (2 μL spore suspension) was placed on WYA-GlcNAc (2 mL/well, in a 12-well assay plate). A paper disk (6 mm; Toyo Roshi Kaisha) containing the test sample was placed on the other side of the inoculation site.…”
Section: Experimental Sectionmentioning
confidence: 99%